Towards a Confucian geopolitics. Issue 2 (July 2021) - An, Ning; Sharp, Jo; Shaw, Ian
In this article, we argue that Confucian philosophies are vital to understanding contemporary Chinese geopolitics. Existing Western geopolitical frameworks, we contend, are insufficient for grasping the complex theories and historical legacies that underpin China's foreign policy. This issue becomes particularly salient as scholars and the public alike try to manage complex and changing geopolitical ideas underpinning the Belt and Road Initiative, recently heralded by the Chinese state and epitomising China's ambition for expanded global engagements. This article provides a much-needed critical assessment and review of Confucian ideas and their uptake in Chinese state theory, geographical imaginations, and geopolitical scripts. While Confucianism typically focuses on ideals of harmony, hierarchy, and normative social order, geopolitics analyses geographical influences on politics – in particular, violence and conflict. However, it is precisely within this contradictory dialectic that new possibilities for analysing the geopolitics of a rising global power can emerge.